(untitled) (Research, Society and Development, 2021)
The present study aims to analyze the hypothesis of fit of the autonomous means of challenge known as rescission action, when configured the hypothesis of art. 966, I, of the Civil Procedure Code, which deals with the decision rendered by virtue of the judge’s malfeasance, concussion or corruption. The objective is to investigate, from the point of view of the Pontian ladder of the plans of the legal act, if the defect of the decision made in these circumstances fulminates the validity or the very existence of the legal act, reaching, in the end, understanding by the second hypothesis. The procedural effects arising from the said finding are analyzed, especially as regards the appropriate instrument for challenge. For this purpose, the deductive method is used, based on the general possibility, contemplated in the above mentioned device, for specific analysis under the prism of the plans of the legal act. It has a methodological objective in its propositional bias. The work will be based on bibliographic research and analysis of the legal text, jurisprudence and academic articles.